DP202216 maize hybrids shift upper limit of C and N partitioning to grain - Palmero, Francisco; Fernandez, Javier A.; Habben, Jeffrey E.; Schussler, Jeffrey R.; Weers, Ben; Bing, James; Hefley, Trevor; Prasad, P. V. Vara; Ciampitti, Ignacio A. (Frontiers in Plant Science, 2025)
Increasing both harvest index (HI) and nitrogen (N) harvest index (NHI) is a promising approach for improving the effective use of resources in grain crops. Previous studies on maize (Zea mays L.) reported increments in different carbon (C)-N physiological and morphological traits in DP202216 hybrids (ZmGos2-zmm28, event DP202216, Corteva Agrisciences). The objectives of this study were to i) identify changes in the maximum limit (potential) of C and N partitioning to the grains (HI and NHI, respectively) in DP202216 maize hybrids at equal plant growth levels, and ii) determine the main factors underpinning the mechanisms associated with any observed changes in C and N partitioning to grains. Two DP202216 hybrids were evaluated with their respective wild-type (WT) controls during two field growing seasons (2022 and 2023) under three N rates (0 kg ha-1, 150 kg ha-1, and 300 kg ha-1). Long-term 15N labeling was used to precisely study N remobilization fluxes. The DP202216 plants showed an increase of 2% and 5% in the upper boundary of the HI and NHI, respectively. Furthermore, the DP202216 hybrids incremented 19% the relative allocation of 15N to grains. This was translated into a higher utilization of N absorbed during vegetative stages in DP202216 hybrids, independently of the amount of N uptake. The hybrids with the DP202216 event increased 9% the number of grains per unit of plant biomass. Our study describes improvements on the upper limit of HI and NHI in DP202216 maize hybrids. We showed that the increase in C and N allocation to the reproductive organs in the DP202216 hybrids was related to higher ‘relative’ C and N demand by the grains. Thus, the DP202216 trait provides a new genetic tool to improve grain yield potential and yield stability via enhanced resource utilization in maize production, offering the farmers the opportunity to maximize return on investment (ROI) for N input costs.